Anastrozole-mediated modulation of mitochondrial activity by inhibition of mitochondrial permeability transition pore opening: an initial perspective - Kumar, Somesh; Choudhary, Neha; Faruq, Mohammed; Kumar, Arun; Saran, Ravindra K; Indercanti, Prem Kumar; Singh, Vikram; Sait, Haseena; Jaitley, Sunita; Valis, Martin; Kuca, Kamil; Polipalli, Sunil K; et al. (Journal of biomolecular structure & dynamics, 2023)
The mitochondrial permeability transition pore (mtPTP) plays a vital role in altering the structure and function of mitochondria. Cyclophilin D (CypD) is a mitochondrial protein that regulates mtPTP function and a known drug target for therapeutic studies involving mitochondria. While the effect of aromatase inhibition on the mtPTP has been studied previously, the effect of anastrozole on the mtPTP has not been completely elucidated. The role of anastrozole in modulating the mtPTP was evaluated by docking, molecular dynamics and network-guided studies using human CypD data. The peripheral blood mononuclear cells (PBMCs) of patients with mitochondrial disorders and healthy controls were treated with anastrozole and evaluated for mitochondrial permeability transition pore (mtPTP) function and apoptosis using a flow cytometer. Spectrophotometry was employed for estimating total ATP levels. The anastrozole-CypD complex is more stable than cyclosporin A (CsA)-CypD. Anastrozole performed better than cyclosporine in inhibiting mtPTP. Additional effects included inducing mitochondrial membrane depolarization and a reduction in mitochondrial swelling and superoxide generation, intrinsic caspase-3 activity and cellular apoptosis, along with an increase in ATP levels. Anastrozole may serve as a potential therapeutic agent for mitochondrial disorders and ameliorate the clinical phenotype by regulating the activity of mtPTP. However, further studies are required to substantiate our preliminary findings.Communicated by Ramaswamy H. Sarma.
Keywords: Mitochondria; transportní proteiny mitochondriální membrány; Mitochondrial Permeability Transition Pore; adenosintrifosfát; peptidylprolylisomerasa F; Humans; Anastrozole; Mitochondrial Diseases; přechodový pór mitochondriální permeability; Cyclophilins; Leukocytes, Mononuclear; cyklofiliny; lidé; anastrozol; mitochondrie; Adenosine Triphosphate; leukocyty mononukleární; Peptidyl-Prolyl Isomerase F; mitochondriální nemoci; Mitochondrial Membrane Transport Proteins